Developing An Integrated Quality Management Model Using Advanced Execution Premium Strategy for Thai Higher Education Institutions - Tongkeo, Tuan; Polsarum, Punsak; Areesophonphichet, Sornnate (Scholar: Human Sciences, 2017)
The purpose of this study was to develop an integrated quality management model using Advanced Execution Premium Strategy. Purposive sampling was adopted in this study. 30 senior managers and staff were chosen from different institutions which received good and very good of IQA from various Thai Higher Education Institutes. Induction and deduction were conducted. Data analysis, mechanism and system that consists of CSIPOCF (Context, Suppliers, Input, Process, Output, Customers and Feedback) was adopted as a framework for integrating quality assurance and management strategy. The research found that the model consists of system and mechanism as the Office of Strategy Management was responsible for coordination and integration of all the management process at policy making level and action level. Database system, strategy development process – strategy plan, action plan, monitoring and learning, evaluation as well as budget were needed for integration process. Integration of strategic management and other concepts - strategic map is the challenged strategy to the competitive global environment in Higher Education Institutes.